2019
DOI: 10.1016/j.lungcan.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutation patterns in a population-based non-small cell lung cancer cohort and prognostic impact of concomitant mutations in KRAS and TP53 or STK11

Abstract: Non-small cell lung cancer (NSCLC) is a heterogeneous disease with unique combinations of somatic molecular alterations in individual patients, as well as significant differences in populations across the world with regard to mutation spectra and mutation frequencies. Here we aim to describe mutational patterns and linked clinical parameters in a population-based NSCLC cohort. Materials and methods: Using targeted resequencing the mutational status of 82 genes was evaluated in a consecutive Swedish surgical NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
117
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 46 publications
17
117
0
3
Order By: Relevance
“…The current data, in a large observational genomic study among patients receiving routine clinical care, support the association of STK11m with poor treatment outcomes previously observed in smaller clinical trial cohorts [18][19][20][21][22][23][24]. Shorter OS and reduced response rates have been observed in patients with STK11m versus STK11wt non-squamous metastatic NSCLC treated with durvalumab (with or without tremelimumab) across multiple phase 1/2 trials [18].…”
Section: Plos Onesupporting
confidence: 79%
See 1 more Smart Citation
“…The current data, in a large observational genomic study among patients receiving routine clinical care, support the association of STK11m with poor treatment outcomes previously observed in smaller clinical trial cohorts [18][19][20][21][22][23][24]. Shorter OS and reduced response rates have been observed in patients with STK11m versus STK11wt non-squamous metastatic NSCLC treated with durvalumab (with or without tremelimumab) across multiple phase 1/2 trials [18].…”
Section: Plos Onesupporting
confidence: 79%
“…PD-L1 expression on tumor cells has been used to guide treatment selection, and more recently tumor mutational burden (TMB) has shown potential as a predictive biomarker for IO benefit [12][13][14][15]. Mutations in individual genes and co-mutation patterns have also been linked to patient response to standard chemotherapy and/or IO in advanced NSCLC [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies demonstrated the role of TP53 mutations in predicting poor prognosis of advanced NSCLC patients [9,[11][12][13][14][15], and this was confirmed also in the subgroup of NSCLC patients carrying EGFR mutations [8,9,16]. In particular, different recent studies showed that the concurrent presence of TP53 mutations negatively affects response to TKIs in EGFR-mutated NSCLC patients, suggesting a role for these gene mutations in determining primary resistance to these drugs [6,7,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 85%
“…The high-throughput sequencing technology has made it possible a comprehensive interrogation of whole transcriptome and genome of tumor tissues at an increasingly reasonable cost [4,5]. Previous studies focused on finding prognostic signatures based on gene expressio n [6][7][8][9] or mutation [10][11][12] for LUAD patients. For example, Li et al [7] reported gene expression-based models with an average C-index of 0.604 on testing datasets from TCGA-LUAD in predicting overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%